IMPROVEMENT OF AN ELECTROMECHANICAL VALVE (EMV) SYSTEM, DYNAMIC ANALYSIS AND DETERMINATION OF WORKING LIMITS AT DIFFERENT LIFTINGS - Nida BIRGÜL (International Journal of Applied Methods in Electronics and Computers, 2017)
In four-cycle internal combustion engines, the valves control the gas inlet and outlet events. Electromechanical valve (EMV) systems perform the required valve timing independently of the crankshaft position. With this feature, EMV systems have a great potential for increasing engine performance, ensuring optimum fuel consumption and minimizing emissions. The intent of this study was to improve an EMV system, which has 12V supply potential, and to investigate dynamic performance at different lifting valve operations and then to determine the support limits of an internal combustion engine.